Impacts of tourism-related establishments in the coastal zone of Bohol and Tawala Panglao, Bohol, Philippines - Tanggaan, Marcial Mangcao (Cebu City University of the Philippines Visayas-Cebu College, 2006)
Panglao Island known for its white sand beaches is being promoter as one of the major tourist destination of the Province of Bohol. This has resulted to the construction boom of tourism facilities specifically at the Southwestern coast of island. It is anticipated that with the vigorous promotion campaign of Bohol as major turist destination and the approval of Panglao Island Tourism Estate Zone on June 23, 2003 by the Philippine Economic Zone Authority more tourism-related facilities would be established in the area. However, if not properly managed, this would lead to unsustainable tourism. There is need therefore to assess first the existing facilities so that whatever information that could be gathered would become the basis in managing future development. To determine the impacts of the existing facilities to the bio-physical as well as the socio-economic environments, the tourism-related facilities were assessed and characterized and their impacts or influence whether positive or negative would therefore be known.For impacts to the biophysical environment, water quality of the swimming areas in terms of E. coli and Total Coliform levels as well as the standing crop biomass of seagrasses were considered. The following component of the socio-economic environment was considered : demographic changes, household income and community income and services. The findings have shown that the sasonality of tourists in the study area have no significant influence in terms of E. coli and TC levels (p>0.05). Based on study results. It is defective septic tanks located within the salvage zone that has great influence to the water quality. The results shows that the number of bathers has no significant effect on seagrasses in terms of above ground standing cop biomass. There is no significant difference between the mean values of the four study sites (p>0.0.05). This means that the status of seagrasses in areas frequented by bathers has no significant difference with those areas that have less number of bathers. In terms of the socio-economic component, the construction boom of tourism facilities had resulted in abnormally high population growth rates of the host communities compared with other barangays that have no or less tourism facilities. Positive influence of tourism is the job opportunities it created. The community has also benefited the services and infrastructures brought about by tourism such as paved roads, telecommunications facilities and a 24-hour world class police precinct. Direct income however is minimal for the host community for it is only the barangay clearance fees and 50% of community tax certificate fees of the approximately 700 employees of the tourism establishments that would go directly to the host barangay. Negative influence however is the high cost of living and the perceived problems of illegal drugs as well as limited access of the residents to some portions of the beach areas due to the practice of some resort owners who fenced their properties.
Thesis (M.S. Environmental Studies) -- Cebu City : U.P. in the Visayas-Cebu College, October 2006.